ANTIDIABETIC EFFECT OF A POLY HERBAL FORMULATION (D) ON HUMAN PANCREATICAMYLASE - K. S. DAYANANDA,; S.M.GOPINATH, (International Journal of Pharma and Bio Sciences, 2013)
Diabetes has become a common global health problem that affects >170million people worldwide. It is one of the leading causes of death and disability. It is estimated that by 2030, the number will rise to 366 million (www.who.int). The majority of diabetes (~90%) is type 2 diabetes (T2D) caused by a combination of impaired insulin secretion from pancreatic beta cells and insulin resistance of the peripheral target tissues, especially muscle and liver., Traditional Medicines obtained from medicinal plants are used by about 40-60% of the world’s population. Though there are many approaches to control diabetes and its secondary complications, herbal formulations are preferred due to lesser side effects and low cost. In this review we have studied the inhibitory effect of a polyherbal formulation consisting of ten antidiabetic herbal plants Gymnemasylvestre, Steviarebaudiana, Momordichacharantia, syzimumcumini, Withaniasomnifera, Tinosporacardiofolia, Ocimumsanturm, Moringaoliefera, Momordica dioica and Phyllanthusemblica,. The aqueous and ethanolic extract showed significant inhibition on human Pancreaticamylase.